OBJECTIVE RIGHTS FOR FINANCING COMPANIES AS FIDUCIARY GUARANTEE HOLDER - Maulana, Ilham; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this research is to explain the objective rights of the Fiduciary Guarantee in the Financing Company. This research uses a normative method using primary, secondary and tertiary legal materials with descriptive analysis and inductive drawing conclusions. As it is known that the Fiduciary Guarantee will basically continue to bind to the Fiduciary Guarantee Object. Fiduciary guarantees given to Financing Companies as creditors receiving fiduciary rights are granted imperfectly. The agreement usually separates the ownership documents that are authorized to the creditor receiving the fiduciary and the object of the guarantee to the debtor providing the fiduciary. The imperfect objective rights have led to a lot of speculation that the owner of the object is the owner who fully controls the object without regard to the existence of ownership documents. For this reason, sometimes finance companies have difficulty in executing the fiduciary guarantee object. The results of the research show that material rights will always follow wherever the owner of the object is, but in this short study it can be seen that every object that is still guaranteed status has a lien which will continue to be attached until the object is paid off by the debtor.